Teoretični izračun mas nukleonov - Kolar-Požun, Andrej (Matrika, 2019)
A convincing confirmation of the quantum chromodynamics (QCD) is an accurate postdiction of the nucleon masses. The article begins by introducing the basic concepts of quantum field theory and discretizing the QCD action. The techniques for evaluation of Euclidean correlators and how they can be used to extract the nucleon masses are then discussed. The results are compared with the measured values of nucleon masses.
Keywords: elementary particle physics; fizika osnovnih delcev; kvantna kromodinamika; mase nukleonov; nucleon masses; quantum chromodynamics